2015
DOI: 10.3109/0886022x.2015.1015427
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rg1 inhibits endoplasmic reticulum stress-induced apoptosis after unilateral ureteral obstruction in rats

Abstract: (2015) Ginsenoside-Rg1 inhibits endoplasmic reticulum stress-induced apoptosis after unilateral ureteral obstruction in rats, Renal Failure, 37:5,[890][891][892][893][894][895] DOI: 10.3109 Aim: Endoplasmic reticulum (ER) stress and unfolded protein response (UPR) are implicated in many fibrotic diseases, including renal fibrosis. Whether Ginsenoside-Rg1 (G-Rg1) could attenuate renal fibrosis via suppression of ER stress and UPR has not been reported. The aim of this study was to explore the effect of G-Rg1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…NGR1 can regulate Akt/Nrf2 pathways or tumor necrosis factor-a via estrogen receptor under the pathologic circumstance Zhong et al, 2015). Li et al (2015) and found that NGR1 could protect from renal injury via inhibition of ER stress. Results of some studies have shown that NGR1 provided neuroprotection in an adult rat model of cerebral ischemia/reperfusion via regulation of Akt/Nrf2 pathways or LC3 and Beclin 1 (Lu et al, 2011;Meng et al, 2104).…”
Section: Introductionmentioning
confidence: 99%
“…NGR1 can regulate Akt/Nrf2 pathways or tumor necrosis factor-a via estrogen receptor under the pathologic circumstance Zhong et al, 2015). Li et al (2015) and found that NGR1 could protect from renal injury via inhibition of ER stress. Results of some studies have shown that NGR1 provided neuroprotection in an adult rat model of cerebral ischemia/reperfusion via regulation of Akt/Nrf2 pathways or LC3 and Beclin 1 (Lu et al, 2011;Meng et al, 2104).…”
Section: Introductionmentioning
confidence: 99%
“…43) We have also observed that G-Rg1 reduced cell apoptosis and TIF in kidney fibrosis. 18,19) G-Rg1 and Klotho are both involved in TIF, and we proposed that the inhibitory effect of G-Rg1 may be related to the Klotho effect. We found that G-Rg1 administration alleviated UUO-associated fibrosis, which was accompanied by alterations in the expression of the TGF-β1/Smad pathway and EMT-related proteins, including upregulation of Smad7, and downregulation of TGF-β1 and p-Smad3.…”
Section: Discussionmentioning
confidence: 95%
“…The UUO rat model was established as previously described. 11) G-Rg1 (68317; Sigma-Aldrich, St. Louis, MO, U.S.A.) was administered to the rats by intraperitoneal injection at a dose of 50 mg/kg per day based on our previous results 18,19) (in our preliminary experiments, 25 mg/kg failed to yield enough beneficial effects and 100 mg/kg failed to yield extra beneficial effects). Klotho knockdown was mediated by short hairpin RNA interference (shRNA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations